2013
DOI: 10.1063/1.4773920
|View full text |Cite
|
Sign up to set email alerts
|

A coarse-grained model for DNA-functionalized spherical colloids, revisited: Effective pair potential from parallel replica simulations

Abstract: We discuss a coarse-grained model recently proposed by Starr and Sciortino [J. Phys.: Condens. Matter 18, L347 (2006)] for spherical particles functionalized with short single DNA strands. The model incorporates two key aspects of DNA hybridization, i.e., the specificity of binding between DNA bases and the strong directionality of hydrogen bonds. Here, we calculate the effective potential between two DNA-functionalized particles of equal size using a parallel replica protocol. We find that the transition from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 108 publications
0
19
0
Order By: Relevance
“…The use of DNA labeling to control binding specificity was originally pioneered for assembling nanoparticles (14)(15)(16)(17) into infinite crystals (18)(19)(20)(21)(22)(23)(24), where recently it was demonstrated that with two species with differing particle radii and DNA linker length a zoo of different crystal morphologies can be created (25). Work at the colloidal scale has begun to bear fruit (13,17,(26)(27)(28)(29)(30). However, the set of possible structures that could be coded is far more general, including structures of any shape and size, both rigid and flexible.…”
mentioning
confidence: 99%
“…The use of DNA labeling to control binding specificity was originally pioneered for assembling nanoparticles (14)(15)(16)(17) into infinite crystals (18)(19)(20)(21)(22)(23)(24), where recently it was demonstrated that with two species with differing particle radii and DNA linker length a zoo of different crystal morphologies can be created (25). Work at the colloidal scale has begun to bear fruit (13,17,(26)(27)(28)(29)(30). However, the set of possible structures that could be coded is far more general, including structures of any shape and size, both rigid and flexible.…”
mentioning
confidence: 99%
“…Classical experiments showed that DNA-based specific interactions allow assembly of crystals of nanoparticles (9)(10)(11)(12). More recently, efforts for self-assembly at the colloidal scale have begun to bear fruit (12)(13)(14)(15)(16)(17)(18). To achieve the exponentially growing catalytic cycles of the current study, we find that it is necessary to use time-dependent interactions between the particles, whose strength can be modulated over a programmable timescale.…”
mentioning
confidence: 85%
“…Various simulation models for DNA chains have been contrived over the last years [132][133][134][135][136][137][138][139][140][141][142][143]. As it usually happens with these models, they aim at reproducing only the properties of interest of the system.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…It has been found for this model that relaxing the condition of kinetically immobile strands on the surface of the particles, a slight increase or decrease in the melting temperature occurs. Larger changes to the melting temperature result from increasing the number of strands, which increases the melting temperature, or by increasing the core NP diameter, which decreases the melting temperature [143]. A quantitative description of the melting temperature has been provided by the model of Starr and Sciortino [142][143][144].…”
Section: Coarse-grained Modelsmentioning
confidence: 99%